The Effect of SFBGT on the Depression Level Among Indonesian Women Migrant Workers in Malaysia - Juwita Purba, Ellys; Mohamad Syed Abdullah, Syed (International Journal of Engineering and Technology, 2018)
So many surveys have demonstrated that there are high degrees of morbidity due to mental turmoil among immigrants, mainly depression and apprehension. Few of these studies unveil that migrant bond mentally depressed for the reason that they are tensed with jobs that was not at par with their educational status. From this context, the likelihood of those individuals with a higher education qualifications to end up doing deadly jobs are high, hence lower their self-respect. Those Women who involved in reformation and increasing role in international labor migration presently amount to 49.6 percent of all labor migrants worldwide. At this time, Malaysia has 2.9 million acknowledged and about 3 million unacknowledged workers with the majority of them from Indonesia 50.9%. On Asia continent, the largest class of female employment is domestic workers. Nevertheless, the domestic sector is regularly not protected by labor and industrial relations laws in the host countries, which makes this set of migrants labor particularly vulnerable to mistreatment hence the depression. Studies have shown that stressful experiences increase one’s susceptibility to diseases and mental health trouble. This research aimed to assess the effectiveness of the interventions using Solution-focused brief group therapy (SFBGT). BDI, the Beck depression inventory tool is  employed to the quasi pre-test and post-test methodology to evaluate the depression level of Indonesian women migrant workers in Penang state of Malaysia. The novel significance is that this study will benefit the Indonesian government in policy preparation that can validate her citizens who are principally searching for greener pasture offshore.
Keywords: Depression; Women migrant workers; Solution focused brief group therapy.